Evaluating the behavior of the Balaroud earth fill dam during impoundment in the final construction stage - Soroush Esmaeili-zadeh; Babak Lashkar-Ara (Journal of Applied Research in Water and Wastewater, 2025)
Increased demand for freshwater and climate change effects have shifted focus to water resource management, highlighting the crucial role of dams in addressing supply and demand challenges. One of the primary challenges associated with newly constructed dams is effectively monitoring them during the initial phase of impounding. This study investigates the combined performance of the first impoundment period of the Balaroud earth-fill dam concurrently with the final embankment levels of the dam structure. It also explores the simultaneous effects of these factors on the monitoring and stability of the Balaroud dam, providing hydrometric data measurements throughout the process. Analysis of data from the instrumentation located at the critical section of the dam revealed minor variations in the majority of standpipe piezometers and rock piezometers during the initial months of impounding. These variations were exclusively influenced by the embankment of the dam structure. Following the completion of the embankment and the subsequent rise in the reservoir level, the trend of pore water pressure changes has become aligned with fluctuations in the reservoir level. The analysis of data from the embankment piezometer and total pressure cells shows a downward trend in the pore water pressure ratio at the beginning of the impounding phase, which subsequently increased following the completion of the embankment activities and the rise in the reservoir level. During the impounding period, both the maximum pore water pressure ratio and the reliability ratio against liquefaction and internal erosion have remained within permissible and acceptable limits. Additionally, a decreasing trend in the arching ratio was observed in relation to the rising embankment level until its completion. However, as the reservoir level increased and the saturation zone expanded, the arching ratio began to rise again, indicating effective stress transfer within the dam structure despite localized arcing at specific instrumentation points.